Javanese Language Phonemic and Lexicon Variations in Pekalongan City: A Dialectological Study - Intan Mustika Sari (University of Surakarta, 2024)
This study aims to investigate the phonemic and lexicon variations of the Pekalongan Javanese dialect appearing in Pekalongan City, Central Java, Indonesia. It utilizes a qualitative descriptive study adopted by Creswell and Creswell as the research design. The data were collected through literature review, auditory perception, and data recording techniques. The interactive data analysis model proposed by Miles and Huberman consists of data collection, data reduction, data display, and conclusion. The results reveal that lexicon variants present in the Pekalongan Western and southern regions have resemblances in phonemic variants of the Javanese language with the linguistic dialects employed by the inhabitants of Pemalang and Banjarnegara. The Arabic vocabulary that Middles Eastern immigrants adopted has a major influence on the linguistic variances in the Northern area. Conversely, no noteworthy linguistic variants were detected in the Eastern portion of Pekalongan City. An implication arising from this research is the necessity for more examination and classification of the morphology and phonology of existing Javanese dialects in Central Java. These results serve as material for further studies related to linguistic studies/ socio-dialectology of the Javanese language and contribute to preserving the cultural richness and diversity of the local language in Pekalongan City.